Life on Board Portuguese Ships in the 16th–18th Centuries: Theorizing Households through History and Archaeology - Tânia Manuel Casimiro; Marco Oliveira Borges (Heritage, 2023)
Recognizing and defining behaviors is among the most challenging objectives of writing narratives about the past, especially when direct testimony and the evidence of agents’ actions are long lost. Typically, archaeologists look at material remains to reconstruct daily activities, while historians read and interpret documents that articulate how agents interacted with their surroundings. Following an interdisciplinary approach combining archaeology and history, the purpose of this paper is to reconstruct how different types of agents co-existed on board Portuguese ships in the Early Modern Age, and how those relations can be interpreted as a household. These ships sailed across different oceans with different purposes and destinations, carrying people, animals, and things, all of which had a level of agency. All these agents led to the development of specific relations and ways of being, characterizing the particular dynamics and associations during voyages.